edge: the emergence of dwarf galaxy scaling relations from cosmological radiation-hydrodynamics simulations - Rey, Martin P.; Taylor, Ethan; Gray, Emily I.; Kim, Stacy Y.; Andersson, Eric P.; Pontzen, Andrew; Agertz, Oscar; Read, Justin I.; Cadiou, Corentin ; 0000-0003-2285-0332; Yates, Robert M.; Orkney, Matthew D.A.; Scholte, Dirk; et al. (Monthly Notices of the Royal Astronomical Society, 2025)
We present a new suite of edge ('Engineering Dwarfs at Galaxy formation's Edge') cosmological zoom simulations. The suite includes 15 radiation-hydrodynamical dwarf galaxies covering the ultrafaint to the dwarf irregular regime () to enable comparisons with observed scaling relations. Each object in the suite is evolved at high resolution () and includes stellar radiation, winds, and supernova feedback channels. We compare with previous edge simulations without radiation, finding that radiative feedback results in significantly weaker galactic outflows. This generalizes our previous findings to a wide mass range, and reveals that the effect is most significant at low. Despite this difference, stellar masses stay within a factor of two of each other, and key scaling relations of dwarf galaxies (size-mass, neutral gas-stellar mass, and gas-phase mass-metallicity) emerge correctly in both simulation suites. Only the stellar mass-stellar metallicity relation is strongly sensitive to the change in feedback. This highlights how obtaining statistical samples of dwarf galaxy stellar abundances with next-generation spectrographs will be key to probing and constraining the baryon cycle of dwarf galaxies.
Publisher Copyright: © 2025 The Author(s).
Keywords: galaxies: dwarf; galaxies: evolution; galaxies: ISM; galaxies: structure; methods: numerical